Phase Transition, Dielectric Relaxation and Impedance Spectroscopy of Perovskite xBa0.95Sr0.05Tio3-(1‒X)BiFe0.9Sm0.1O3 Ceramics - Miah, MJ; Mazumder, SC; Hossain, AKM Akther (Bangladesh Journal of Physics, 2020)
Polycrystalline xBa0.95Sr0.05TiO3-(1‒x)BiFe0.9Sm0.1O3[xBST-(1‒x)BFSO] ceramics were synthesized. The structural phase transitions were studied and it was found that structure of the compound transformed from rhombohedral to cubic phase. The compound exhibited a dielectric anomaly in the vicinity of Néel temperature of BiFeO3 except for x = 0.25. Enhanced dielectric properties were noticed and this might be attributed to the reduction of oxygen vacancies. Studies of electrical conductivity over a wide temperature range showed that the ceramics behaved like a semiconductor with the negative temperature coefficient of resistance. Contribution of grains in conduction mechanism of the materials dominated and the grain resistance was found to be decreased with the increase in temperature. A Non-Debye type relaxation was seen in the material. The impedance data were re-plotted using the modulus formulae to avoid the ambiguity arising out of the presence of grain/grain boundary effect. Activation energy was found to be 0.18 to 0.33 eV in modulus study which was very close to complex impedance observation and it was implied that the charge carrier had the same energy barrier during the relaxation. Bangladesh Journal of Physics, 27(1), 23-42, June 2020